Laparoscopic treatment of the peritoneo-vaginal duct persistences in children at Sylvanus Olympio Teaching Hospital of Lomé (Togo) - Akakpo-Numado Gamedzi Komlatsè; Boume Missoki Azanledji; Mihluedo-Agbolan Komlan Anani; Adabra Komlan; Tekou Hubert (Wolters Kluwer Medknow Publications, 2014)
Background: The treatment of the persistent peritoneo-vaginal duct (PPVD) or persistent processus vaginalis (PPV) in children by inguinal access carries a real testicular risk that can be avoided using the laparoscopic treatment, mostly in the case of recurrence. We hereby present the results of our first series treated by laparoscopy at Sylvanus Olympio Teaching Hospital. Patients and Methods: This is a descriptive and prospective study on a 6 months period. It concerned 21 boys with mean age of 4 years and 3 months, weighing 15.70 Kg. They clinically presented 12 unilateral inguinal hernias and 9 hydroceles among which one recurrence. We used the Montupet and Esposito technique. The results were considered good in absence of recurrence and bad if recurrence occurred. Results: With 4 over the 21 patients (19.04%), the diagnosis of a controlateral PPV was done per operatory. In those cases, the bilateral closure was systematic in the same operative time. The mean duration of the unilateral treatment was 57.6 minutes (extremes: 45 and 70 min). The mean pneumo-peritoneum pressure was 7.62 mm Hg (extremes: 5 and 8 mm Hg). Seventeen boys (80.95%) got out on the same day. There was neither infection nor parietal hematoma. With a mean follow-up of 9.3 months, there was no recurrence. Conclusion: The laparoscopic treatment of the PVDP in children is an efficient procedure. It permits to diagnose and treat at the same time, a controlateral PVDP that had not been found during the clinical examination; it also helps to avoid the traumatisms of the spermatic cord.